The influence on capillary diameter solubility of carbon dioxide in water - Prohorov, Alexander; Svitlyk, Andriy; Dolomakin, Yuriy (My University, 2016)
The functional dependence on the influencing factors of carbon dioxide solubility in water.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; вуглекислота; капіляр; пористий капіляр; розчинність; углекислота; капилляр; пористый капилляр; растворимость; carbon dioxide; capillary; porous capillary; solubility